Nanoenergetic Materials Preparation, Properties, and Applications - Trache, Djalal; Deluca, Luigi T. (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This highly informative and carefully presented book discusses the preparation, processing, characterization and applications of different types of nanoenergetic materials, as well as the tailoring of their properties. It gives an overview of recent advances of outstanding classes of energetic materials applied in the fields of physics, chemistry, aerospace, defense, and materials science, among others. The content of this book is relevant to researchers in academia and industry professionals working on the development of advanced nanoenergetic materials and their applications.